Aplikasi terapi seni ekspresif resiliensi diri (TSE-RD) dalam kalangan ibu tunggal kategori De Facto Single Mothers (DFSM) - Nathir, Mehamad (2022)
The application of the Self-Resilience Art Therapy Module (TSE-RD) in group interventions can facilitate Helping Professionals explore issues faced by abandoned single mothers (De Facto Single Mothers - DFSMs) who assume the roles of the family head while their husbands serve prison sentences. The DFSMs’ life under these circumstances is challenging, as they are prone to marginalization and receive little support from the surrounding community. As a result, they often face great pressure in shouldering the responsibilities as the family head. This study aims to understand their experiences and explore their interpretations of the self-resilience elements featured in the TSE-RD Module and examine the Module’s potential application in cluster interventions. The study participants comprise eight DFSMs selected through purposive sampling. Data we obtained using semi-structured in-depth interview methods and document analysis for data triangulation purposes. The TSE-RD Module was implemented in a structured group involving seven therapy session meetings and one interview session meeting for eight weeks. Findings from the study’s thematic analysis show that the DFSMs gained positive experiences throughout the group intervention sessions using the TSE-RD Module. The module successfully explores the interpretations of six elements that constitute the DFSMs self-resilience which are: self-reliance, life meaning, peace of mind and feelings, perseverance, loneliness philosophy and solitude, and divinity and spirituality. In addition, five themes were generated from the TSE-RD Module application on self-resilience, namely new thinking and perceptions, emotional care and stabilization, building single mothers’ self-resilience, decision-making skills and abilities as well as the benefits of creative methods to be shared with other single mothers. The TSE-RD Module resulting from this study is an alternative approach to Helping Professionals in implementing single mothers’ well-being intervention programs for DFSMs in Malaysia. The activities contained in the TSE-RD Module can help DFSMs deal effectively with life’s challenges.